Preparation method and application of iron-nickel doped carbon nanotube
By assembling Fe/Ni-MIL-88B into electrospun nanofibers and pre-oxidizing and carbonizing, iron-nickel-doped carbon nanotubes were prepared, which solved the problems of low dispersion and low catalytic activity of the existing electrocatalyst, and achieved better electrocatalytic performance and low cost preparation methods.
Patent Information
- Application Number
- CN202411951855.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing transition metal-doped carbon nanostructured oxygen reduction electrocatalysts have problems with low dispersion and low catalytic activity.
Iron-nickel-doped carbon nanotubes were prepared by assembling Fe/Ni-MIL-88B into electrospun nanofibers and pre-oxidized and carbonized. This method improves the catalytic effect and conductivity of the catalyst through synergistic effects between bimetals and carbon nanotubes derived from the fiber surface.
The electrocatalytic performance of iron-nickel doped carbon nanotubes is improved, and the preparation method is simple, the raw materials are cheap, and it is suitable for large-scale production.
Smart Images

Figure CN119753741A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional nanomaterials, mainly to the technical field of electrocatalytic materials, and specifically to a preparation method and application of iron-nickel doped carbon nanotubes. Background Art
[0002] With the rapid development of economy, fuel cells have received extensive attention, but the slow kinetics of oxygen reduction reaction hinders the use of batteries. Currently, the most widely used precious metal catalysts in commercial applications are Pt, Ru, Ir and their oxides, but their lack of resources, high cost and easy poisoning limit their large-scale use. Therefore, it is very important to develop cheap, efficient and stable non-precious metal electrocatalysts.
[0003] Transition metals have become promising electrocatalysts because of their key advantages of high metal atom utilization efficiency, high intrinsic activity and low cost. Metal-organic framework materials MOF have attracted widespread attention due to their unique physical and chemical properties such as large specific surface area, high porosity, and precise control of components. Studies have shown that nickel-based metal-organic framework materials can be used as excellent electrocatalysts, and can also be used as excellent substrate materials for carrying other guest substances such as metals, metal oxides, and carbon materials. The invention patent with application number 202010878624.9 provides a Ni-MOF thin film photocatalyst grown in situ on the surface of nickel foam. The invention enables nickel foam to release nickel ions under voltage and self-assemble with 2-methylimidazole in the electrolyte. The resulting photocatalyst can degrade VOCs in the atmosphere under the drive of sunlight and has good photocatalytic activity and stability. The invention patent with application number 202111327404.8 discloses a modulated nickel / cobalt bimetallic MOF-based electrocatalyst, which includes a conductive substrate and a nickel / cobalt bimetallic MOF modulated by ferrocenecarboxylic acid loaded on its surface, and has excellent electrocatalytic activity in urea oxidation reaction. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a method for preparing iron-nickel doped carbon nanotubes, and the technical problem to be solved is that the existing transition metal doped carbon nanostructure oxygen reduction electrocatalysts generally have the problems of low dispersion and low catalytic activity. The applicant believes that doping nickel into iron-based catalysts can effectively adjust the electronic structure and improve the conductivity, but this catalyst is easy to agglomerate and disorderly arranged during the preparation process, thereby affecting the electrochemical performance and stability of the product. At present, it is very important to design a transition metal doped carbon nanostructure catalyst with high dispersion, high performance and microscopically ordered arrangement.
[0005] In order to solve the above technical problems, the present invention assembles Fe / Ni-MIL-88B into electrospun nanofibers, and then pre-oxidizes and carbonizes to synthesize iron-nickel doped carbon nanotubes, wherein Fe / Ni-MIL-88B is used as the main source of the two components, and the synergistic effect between the two components can effectively improve the catalytic effect of the catalyst, and the carbon nanotubes derived from the fiber surface enhance the conductivity of the catalyst and promote electron transfer. Therefore, the iron-nickel doped carbon nanotube material of the present invention has more excellent electrocatalytic performance, and the preparation method of the present invention has the advantages of cheap raw material price and simple operation, and can be applied to large-scale production.
[0006] Specifically, to achieve the above purpose, the present invention provides the following technical solutions:
[0007] A method for preparing iron-nickel doped carbon nanotubes, characterized in that it comprises the following steps:
[0008] (1) Using a substance containing iron salt, nickel salt and terephthalic acid as raw materials, Fe / Ni-MIL-88B metal organic framework material was prepared by a hydrothermal method;
[0009] (2) dispersing Fe / Ni-MIL-88B in N,N-dimethylformamide and adding polyacrylonitrile to form a spinning solution;
[0010] (3) spinning the spinning solution to obtain a polyacrylonitrile fiber film containing Fe / Ni-MIL-88B;
[0011] (4) The obtained polyacrylonitrile fiber film is placed in air for oxidation, and then carbonized in a nitrogen atmosphere to obtain the iron-nickel doped carbon nanotubes.
[0012] Preferably, in the above preparation method, in step (1), the Fe / Ni-MIL-88B metal organic framework material is prepared by a method comprising the following steps:
[0013] A substance containing iron salt, nickel salt and terephthalic acid is used as a raw material, added into N,N-dimethylformamide, mixed evenly to form a mixed solution, and a sodium hydroxide solution is added, mixed evenly to obtain a reaction solution, and a hydrothermal reaction is carried out at 100-150° C. to obtain a Fe / Ni-MIL-88B metal organic framework material.
[0014] Preferably, in the above preparation method, the molar ratio of iron element to nickel element in the raw material is (0.5-2.5):1, preferably (0.5-1.3):1, and more preferably (1.0-1.3):1.
[0015] Preferably, in the above preparation method, the molar ratio of the total amount of iron and nickel elements in the raw materials to terephthalic acid is (2-3.5):1, preferably (2.0-2.5):1.
[0016] Preferably, in the above preparation method, in step (1), the molar ratio of the sum of the iron element and the nickel element to sodium hydroxide is (2.5-4.5):1, preferably (2.5-4.0):1.
[0017] Preferably, in the above preparation method, in step (1), the iron salt is selected from ferric chloride; and the nickel salt is selected from nickel chloride or nickel nitrate.
[0018] Preferably, in the above preparation method, in step (1), the concentration of the iron salt in the mixed solution is 0.05 to 0.12 g / mL, preferably 0.05 to 0.06 g / mL.
[0019] Preferably, in the above preparation method, in step (1), the concentration of the nickel salt in the mixed solution is 0.040 to 0.10 g / mL, preferably 0.045 to 0.05 g / mL.
[0020] Preferably, in the above preparation method, in step (1), the concentration of terephthalic acid in the mixed solution is 0.03 to 0.05 g / mL.
[0021] Preferably, in the above preparation method, the temperature of the hydrothermal reaction is 100-150°C, and the reaction time is 3-15h; preferably 100-120°C, and the reaction time is preferably 3-5h.
[0022] Preferably, in the above preparation method, in step (2), the usage ratio of polyacrylonitrile, N,N-dimethylformamide and Fe / Ni-MIL-88B is 1g:(8-10)mL:(1-2)g, preferably 1g:(9-10)mL:(1.4-1.6)g.
[0023] Preferably, in the above preparation method, step (2) comprises the following steps: dispersing Fe / Ni-MIL-88B in N,N-dimethylformamide, adding polyacrylonitrile, and stirring at a speed of 300 rpm to 500 rpm for 10 to 15 hours to prepare a spinning solution.
[0024] Preferably, in the above preparation method, in step (3), the spinning process includes the following steps: sucking the spinning solution into the syringe of the spinning machine for spinning; wherein the voltage of the spinning process is 15 to 20 kV (preferably 19 kV), the distance from the syringe needle to the collecting copper mesh is 10 to 20 cm (preferably 15 cm), and the speed of the syringe is 0.5 to 0.8 mL / h.
[0025] Preferably, in the above preparation method, in step (4), the temperature of the oxidation process is 200-300°C, preferably 240-260°C, the oxidation time is 1-3h, and the obtained sample is cooled to room temperature after oxidation.
[0026] Preferably, in the above preparation method, in step (4), the carbonization process comprises the following steps:
[0027] The sample obtained after oxidation is placed downstream of a tube furnace, melamine is placed upstream, nitrogen is introduced, and calcination is performed at 700-900°C to complete the carbonization process.
[0028] Preferably, in the above preparation method, the mass ratio of melamine to the sample obtained after oxidation is (5-20):1, preferably (8-10):1.
[0029] Preferably, in the above preparation method, the temperature of the carbonization process is 700-900°C, preferably 700-800°C, and the time is 2-4h.
[0030] Preferably, in the above preparation method, in step (4), the heating rate of the oxidation process is 1 to 5°C / min, preferably 1 to 2°C / min, and the heating rate of the carbonization process is 1 to 5°C / min, preferably 4 to 5°C / min.
[0031] The present invention also provides an iron-nickel doped carbon nanotube, characterized in that it is prepared by the above method.
[0032] Preferably, the iron-nickel doped carbon nanotubes contain carbon, nitrogen, oxygen, iron and nickel, the atomic percentage of the iron element is 0.85-1.20 at%, preferably 1.00-1.20 at%; the atomic percentage of the nickel element is 0.90-1.50 at%, preferably 0.90-1.10 at%.
[0033] Preferably, in the iron-nickel doped carbon nanotubes, the atomic percentage of nitrogen is 7.0 to 8.0 at %, preferably 7.2 to 7.8 at %.
[0034] Preferably, the iron-nickel doped carbon nanotubes are loaded with an iron-nickel alloy, wherein the molar ratio of iron element to nickel element in the iron-nickel alloy is 0.64:0.36.
[0035] Preferably, in the above preparation method, the Fe / Ni-MIL-88B metal organic framework material obtained in step (1) has a length of 200-300 nm and a width of 100-150 nm.
[0036] The present invention also provides an oxygen reduction reaction electrode, characterized in that it comprises an oxygen reduction reaction electrocatalyst, and the electrocatalyst comprises iron-nickel doped carbon nanotubes.
[0037] The present invention also provides the use of the iron-nickel doped carbon nanotubes or the oxygen reduction reaction electrodes in the field of electrocatalytic oxygen reduction reactions.
[0038] The advantages of the present invention are: the present invention assembles Fe / Ni-MIL-88B into electrospun nanofibers, and then calcines to obtain iron-nickel doped carbon nanotubes, wherein the synergistic effect between the bimetallics can effectively improve the catalytic effect of the catalyst, and the carbon nanotubes derived from the fiber surface enhance the conductivity of the catalyst and promote electron transfer. Therefore, the iron-nickel doped carbon nanotube material of the present invention has more excellent electrocatalytic performance, and the preparation method of the present invention has the advantages of cheap raw material price and simple operation, and can be applied to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a transmission electron microscope image of the Fe / Ni-MIL-88B particles obtained in Example 1.
[0040] Figure 2 This is the XRD pattern of the Fe / Ni-MIL-88B particles obtained in Example 1.
[0041] Figure 3 This is a transmission electron micrograph of the PAN / Fe / Ni-MIL-88B polyacrylonitrile nanofibers obtained in Example 1.
[0042] Figure 4 This is a scanning electron microscope image of the iron-nickel doped carbon nanotube material obtained in Example 1.
[0043] Figure 5 This is a transmission electron microscope image of the iron-nickel doped carbon nanotube material obtained in Example 1.
[0044] Figure 6 This is the XRD spectrum of the iron-nickel doped carbon nanotube material obtained in Example 1.
[0045] Figure 7 This is the LSV curve of the iron-nickel doped carbon nanotube material obtained in Example 1.
[0046] Figure 8 This is a transmission electron microscope image of the iron-nickel doped carbon nanotube material obtained in Example 5. DETAILED DESCRIPTION
[0047] In view of the low dispersion of existing transition metal-doped carbon nanostructure oxygen reduction electrocatalysts and the need to improve catalytic activity, the present invention provides an iron-nickel doped carbon nanotube that can be used as a catalyst in the electrocatalytic oxygen reduction process, such as being made into an oxygen reduction reaction electrode.
[0048] In a preferred embodiment, the method for preparing iron-nickel doped carbon nanotubes of the present invention comprises the following steps:
[0049] (1) Fe / Ni-MIL-88B was prepared by hydrothermal method in N,N-dimethylformamide solvent;
[0050] (2) dispersing Fe / Ni-MIL-88B in N,N-dimethylformamide, adding polyacrylonitrile, and stirring to form a spinning solution;
[0051] (3) spinning the obtained spinning solution to obtain a polyacrylonitrile fiber film of PAN / Fe / Ni-MIL-88B;
[0052] (4) The obtained fiber film is placed in an inert gas atmosphere for calcination to obtain iron-nickel doped carbon nanotubes.
[0053] Furthermore, in the above step (1), the preparation method of Fe / Ni-MIL-88B comprises the following steps: pouring iron salt, nickel salt and terephthalic acid into N,N-dimethylformamide and stirring evenly to obtain a reaction solution; hydrothermally reacting the reaction solution at 100-150°C for 3-15h (preferably 100°C for 3h) to obtain Fe / Ni-MIL-88B; in the reaction solution: the concentration of iron salt is 0.054-0.108g / mL (preferably 0.054g / mL), the concentration of nickel salt is 0.0474-0.0948g / mL (preferably 0.0474g / mL), and the concentration of terephthalic acid is 0.033g / mL. The iron salt is preferably ferric chloride hexahydrate, and the nickel salt is preferably nickel chloride hexahydrate. In step (4), the carbonization rate is 1-5°C / min, preferably 4-5°C / min.
[0054] In another preferred embodiment, the method for preparing the iron-nickel doped carbon nanotubes of the present invention comprises the following steps:
[0055] (1) Fe / Ni-MIL-88B was prepared by hydrothermal method in N,N-dimethylformamide solvent;
[0056] (2) ultrasonically dispersing Fe / Ni-MIL-88B in N,N-dimethylformamide, adding polyacrylonitrile, and stirring to form a spinning solution;
[0057] (3) spinning the obtained spinning solution to obtain a polyacrylonitrile fiber film of PAN / Fe / Ni-MIL-88B;
[0058] (4) The obtained fiber film is placed in air for oxidation first, and then carbonized in an inert atmosphere to obtain Fe-Ni doped carbon nanotubes.
[0059] Furthermore, in the above step (1), the preparation method of Fe / Ni-MIL-88B comprises the following steps: adding iron salt, nickel salt and terephthalic acid to N,N-dimethylformamide and stirring evenly to obtain a mixed solution, then adding NaOH solution and stirring evenly to obtain a reaction solution; hydrothermally reacting the reaction solution at 100-150°C for 3-15h to obtain Fe / Ni-MIL-88B; in the mixed solution: the concentration of iron salt is 0.05-0.06g / mL, the concentration of nickel salt is 0.045-0.05g / mL, and the concentration of terephthalic acid is 0.033g / mL.
[0060] Furthermore, in the above step (2), the usage ratio of polyacrylonitrile, N,N-dimethylformamide and Fe / Ni-MIL-88B is 1g:8-10mL:1-2g, preferably 1g:10mL:1.5g.
[0061] Furthermore, in the above step (3), the spinning voltage is 15-20 kV (preferably 19 kV), and the distance from the spinning needle to the collecting copper mesh is 10-20 cm (preferably 15 cm).
[0062] Furthermore, in the above step (4), the inert gas used is nitrogen, and the calcination is divided into two steps: first, the temperature is raised from 30°C to 200-300°C in air and calcined for 1-3 hours, and then the temperature is raised from 30°C to 700-900°C in nitrogen and calcined for 2-4 hours.
[0063] In another preferred embodiment, the present invention further provides an oxygen reduction reaction electrode prepared from iron-nickel doped carbon nanotubes; preferably, the electrode is a glassy carbon electrode with the iron-nickel doped carbon nanotube material coated on the surface.
[0064] In the present invention, electrospinning technology is widely used due to its unique three-dimensional structure, and has the advantages of high aspect ratio, large specific surface area and high flexibility. Studies have shown that when the catalyst contains two metals, the synergistic effect between the active sites of the two metals can enhance the catalytic activity. At the same time, the pore structures produced by the pyrolysis of different types of metal organic frameworks are different. By adjusting the ratio of different metal salts, the microstructure and active sites of the derivative materials can be effectively regulated, thereby improving the catalytic performance of the materials; and the pyrolysis temperature of the metal salts of the same proportion will also have a significant impact on their structure. Therefore, the present invention provides a method for preparing iron-nickel doped carbon nanotubes, which mainly includes: assembling the metal organic framework into nanofibers by an electrospinning method, and then pyrolyzing to prepare porous carbon nanofiber materials. The volatilization of organic matter during the pyrolysis process will produce a pore structure, which increases the specific surface area and active sites of the material. In summary, the preparation method is low in cost, and the resulting product has a high specific surface area, a porous structure, and more active sites, which can greatly improve the catalytic performance.
[0065] The Fe / Ni-MIL-88B described in the present invention refers to a MIL-type metal organic framework material synthesized from iron salt, nickel salt and terephthalic acid, which has a one-dimensional rod-like structure.
[0066] The iron-nickel doped carbon nanotubes and the preparation method and application thereof of the present invention are further described below through specific examples.
[0067] In the following examples, all reagents used were purchased from Sinopharm Reagents.
[0068] The information of the instruments used in the examples is shown in the following table:
[0069] Table 1 Instrument information
[0070] Reagents / Instruments Specifications / Models Manufacturer / Source Electric constant temperature drying oven DHG-9145A Shanghai Jinghong Experimental Equipment Co., Ltd. Magnetic stirrer 85-2B Guangzhou Yike Laboratory Technology Co., Ltd. Spinning Machine E05-001 Foshan Lepton Tube Furnace OTF-1200X Hefei Kejing Scanning electron microscopy Zeiss Supra 40 Carl Zeiss, Germany X-ray diffractometer X'Pert PRO MPD PANalytical X-ray Photoelectron Spectrometer ESCALAB250Xi Thermo
[0071] Example 1
[0072] In this embodiment, the preparation process of iron-nickel doped carbon nanotubes is as follows:
[0073] (1) 3.24 g FeCl3·6H2O, 2.844 g NiCl2·6H2O, 1.99 g terephthalic acid (H2BDC) and 60 mL DMF were weighed and mixed, and stirred at 400 rpm for 10 min. 4.8 mL 2M NaOH solution was added to the above solution, and stirred at 400 rpm for 15 min. The mixture was poured into a 100 mL autoclave and kept in an oven at 100°C for 3 h. The mixture was then cooled to room temperature and centrifuged at 6000 rpm for 5 min. The mixture was washed with DMF and anhydrous ethanol and centrifuged respectively, and dried in a vacuum oven at 70°C for 12 h to obtain Fe / Ni-MIL-88B material.
[0074] (2) 1.5 g of Fe / Ni-MIL-88B was weighed and added to 10 mL of DMF. The mixture was dispersed by ultrasonication for 2 h. 1 g of polyacrylonitrile (PAN) was added and stirred at 400 rpm overnight to prepare a spinning solution.
[0075] (3) The obtained spinning solution was sucked into the syringe of the spinning machine, the distance between the needle and the collecting net was 15 cm, the spinning voltage was 19 kV, the spinning syringe rate was 0.5 mL / h, and the spun film was collected every two hours to obtain PAN / Fe / Ni-MIL-88B polyacrylonitrile nanofiber film.
[0076] (4) The obtained PAN / Fe / Ni-MIL-88B polyacrylonitrile nanofiber film is first oxidized and then calcined under inert gas: first, the temperature is increased to 260°C at a heating rate of 1°C / min in air and kept at this temperature for 2 h, then cooled to room temperature, and then the obtained sample is placed in the downstream of a tubular furnace, and melamine is placed in the upstream, with a mass ratio of melamine to sample of 10:1. Nitrogen is introduced, and the temperature is increased from 30°C to 800°C at a heating rate of 5°C / min and kept at this temperature for 2 h. After the product is ground, an iron-nickel doped carbon nanotube material is obtained.
[0077] The reaction mechanism of this embodiment is: small-sized nanorods are installed into fibers through electrospinning technology, organic matter is evaporated at high temperature, leaving only metal and nitrogen and carbon-doped nanofiber materials, and finally iron-nickel-doped carbon nanotube materials are produced.
[0078] Figure 1 This is a transmission electron microscope image of the Fe / Ni-MIL-88B particles obtained in this example. It can be seen that the overall structure is a long rod with a length of 200-300nm and a width of 100-150nm.
[0079] The Fe / Ni-MIL-88B particles obtained in this example were subjected to XRD detection. The detection conditions were: Cu target, Kα=1 / 1.54056, scanning angle 2θ=5-80°, scanning speed 5°min -1 .
[0080] Figure 2 This is the XRD spectrum of the Fe / Ni-MIL-88B particles obtained in step (1) of this embodiment. Compared with the standard spectrum of Fe-MIL-88B, it can be seen that the material obtained in step (1) of this embodiment is Fe / Ni-MIL-88B material.
[0081] Figure 3This is a transmission electron microscope image of the PAN / Fe / Ni-MIL-88B polyacrylonitrile nanofiber obtained in this example. It can be seen that the spinning surface is relatively rough, which is mainly caused by the roughness after the nanorods are spun into it.
[0082] Figure 4 This is a scanning electron microscope image of the iron-nickel doped carbon nanotube material obtained in this example. It can be seen that after fiber-shaped spinning and calcination, the main morphology still maintains a thin rod shape, and there are carbon nanotubes on the surface.
[0083] Figure 5 This is a transmission electron microscope image of the iron-nickel doped carbon nanotube material obtained in this example. It can be clearly seen that there are particles and voids inside, which are mainly caused by the volatilization of organic matter in the spun fibers, and there are derived carbon nanotubes on the surface.
[0084] Figure 6 The XRD pattern of the Fe-Ni doped carbon nanotube material obtained in this example is shown in the standard card PDF#47-1405, i.e., Fe 0.64 Ni 0.36 By comparison, it can be seen that the iron-nickel doped carbon nanotubes obtained in this embodiment contain alloy Fe 0.64 Ni 0.36 .
[0085] The iron-nickel doped carbon nanotube material obtained in this example was subjected to X-ray photoelectron spectroscopy (XPS) detection. The detection results showed that the product was composed of C, N, O, Fe, and Ni elements, the atomic percentage of carbon element was 83.43 at%, the atomic percentage of nitrogen element was 7.49 at%, the atomic percentage of oxygen element was 6.95 at%, the atomic percentage of iron element was 1.17 at%, and the atomic percentage of nickel element was 0.96 at%.
[0086] The electrocatalytic performance of the Fe-Ni doped carbon nanotubes obtained in the example was tested as follows: the electrochemical test was performed using a three-electrode system in an electrochemical workstation, and the working electrode was a glassy carbon disk electrode with a diameter of 5 mm (the area of the disk was 0.196 cm 2 ), the reference electrode is Hg / HgO electrode, and the carbon rod electrode is used as the counter electrode. Take 5 mg of the obtained nanofibers and disperse them in 490 μL of ethanol, add 10 μL of naphthol solution, ultrasonicate for 3 hours, and then use a microsyringe to take 15 μL and apply it on the glassy carbon surface. Before the test, O2 is passed into the electrolyte (0.1M KOH solution) for at least half an hour to make the electrolyte saturated with O2. During the test, the speed of the rotating disk electrode is set to 1600 rpm, the scanning speed is 5 mV / s, the test voltage is -0.9~0.3 V (Hg / HgO), and the CV curve is tested ten times when testing the catalyst performance.
[0087] Figure 7This is the LSV curve of the iron-nickel doped carbon nanotubes obtained in Example 1. It can be seen that the half-wave potential of the target product obtained in Example 1 is 0.87 V, indicating that the obtained iron-nickel doped carbon nanotubes have excellent electrocatalytic properties and can be used as an electrocatalyst for oxygen reduction reaction.
[0088] Example 2
[0089] In this comparative example, iron-nickel doped carbon nanotubes were prepared in a similar manner to that in Example 1, except that step (1) was:
[0090] Weigh 3.24g FeCl3·6H2O, 5.688g NiCl2·6H2O, 1.99g terephthalic acid (H2BDC) and 60mL DMF, mix, stir at 400rpm for 10 minutes, add 4.8mL 2M NaOH solution to the above solution, stir at 400rpm for 15 minutes, pour into a 100mL autoclave, keep in a 100℃ oven for 3h, then cool to room temperature, centrifuge at 6000rpm for 5min in a centrifuge, wash and centrifuge with DMF and anhydrous ethanol respectively, and dry in a 70℃ vacuum drying oven for 12h to obtain Fe / Ni-MIL-88B material.
[0091] The LSV curve of the sample was measured in the same manner as in Example 1. The results showed that when the iron-nickel doped carbon nanotubes obtained in Example 2 were used as an electrocatalyst, the half-wave potential was 0.82V.
[0092] Example 3
[0093] In this embodiment, iron-nickel doped carbon nanotubes are prepared in a similar manner to that in embodiment 1, except that step (1) is:
[0094] Weigh 6.48g FeCl3·6H2O, 2.844g NiCl2·6H2O, 1.99g terephthalic acid (H2BDC) and 60mL DMF, mix, stir at 400rpm for 10 minutes, add 4.8mL 2M NaOH solution to the above solution, stir at 400rpm for 15 minutes, pour into a 100mL autoclave, keep in a 100℃ oven for 3h, then cool to room temperature, centrifuge at 6000rpm for 5min, wash with DMF and anhydrous ethanol, centrifuge, and dry in a 70℃ vacuum oven for 12h to obtain Fe / Ni-MIL-88B material.
[0095] The LSV curve of the sample was measured in the same manner as in Example 1. The results showed that when the iron-nickel doped carbon nanotubes obtained in this example were used as an electrocatalyst, the half-wave potential was 0.79V.
[0096] Example 4
[0097] In this embodiment, iron-nickel doped carbon nanotubes are prepared in a similar manner to that in embodiment 1, except that step (1) and step (4) are respectively:
[0098] (1) Weigh 3.24 g FeCl3·6H2O, 3.48 g Ni(NO3)2·6H2O, 1.99 g terephthalic acid (H2BDC) and 60 mL DMF, mix them, stir at 400 rpm for 10 min, add 4.8 mL 2M NaOH solution into the above solution, stir at 400 rpm for 15 min, pour into a 100 mL autoclave, keep in an oven at 120°C for 3 h, then cool to room temperature, centrifuge at 6000 rpm for 5 min, wash with DMF and anhydrous ethanol, centrifuge, and dry in a vacuum oven at 70°C for 12 h to obtain Fe / Ni-MIL-88B material.
[0099] (4) The obtained PAN / Fe / Ni-MIL-88B polyacrylonitrile nanofiber film is first oxidized and then calcined under inert gas: first, the temperature is increased to 200°C at a heating rate of 1°C / min in air and kept at this temperature for 3 h, then cooled to room temperature, and then the obtained sample is placed in the downstream of a tubular furnace, and melamine is placed in the upstream, with a mass ratio of melamine to sample of 8:1. Nitrogen is introduced, and the temperature is increased from 30°C to 800°C at a heating rate of 5°C / min and kept at this temperature for 2 h. After the product is ground, an iron-nickel doped carbon nanotube material is obtained.
[0100] The LSV curve of the sample was detected in the same manner as in Example 1. The results showed that when the iron-nickel doped carbon nanotubes obtained in this example were used as an electrocatalyst, the half-wave potential was 0.81V.
[0101] Example 5
[0102] In this embodiment, iron-nickel doped carbon nanotubes are prepared in a similar manner to that in embodiment 1, except that step (1) is:
[0103] Weigh 3.24g FeCl3·6H2O, 2.844g NiCl2·6H2O, 1.99g terephthalic acid (H2BDC) and 60mL DMF, mix, stir at 400rpm for 10 minutes, add 4.8mL 2M NaOH solution to the above solution, stir at 400rpm for 15 minutes, pour into a 100mL autoclave, keep in an oven at 100℃ for 15h, then cool to room temperature, centrifuge at 6000rpm for 5min in a centrifuge, wash and centrifuge with DMF and anhydrous ethanol respectively, and dry in a vacuum drying oven at 70℃ for 12h to obtain Fe / Ni-MIL-88B material.
[0104] Figure 8This is a transmission electron microscope image of the Fe / Ni-MIL-88B material obtained in this example. It can be seen from the image that the obtained MOF material is in the shape of a long rod with a length of 800nm to 1.5μm and a width of 100-200nm.
[0105] Example 6
[0106] In this embodiment, iron-nickel doped carbon nanotubes are prepared in a similar manner to that in embodiment 1, except that step (1) is:
[0107] Weigh 3.24g FeCl3·6H2O, 2.844g NiCl2·6H2O, 1.99g terephthalic acid (H2BDC) and 60mL DMF, mix, stir at 400rpm for 10 minutes, add 4.8mL 2M NaOH solution to the above solution, stir at 400rpm for 15 minutes, pour into a 100mL autoclave, keep in an oven at 150℃ for 5h, then cool to room temperature, centrifuge at 6000rpm for 5min in a centrifuge, wash and centrifuge with DMF and anhydrous ethanol respectively, and dry in a vacuum drying oven at 70℃ for 12h to obtain Fe / Ni-MIL-88B material.
[0108] From the transmission electron microscopy image of the Fe / Ni-MIL-88B material obtained in this example, it can be seen that the obtained MOF material is in the shape of a long rod with a length of 1.0 μm to 1.5 μm and a width of 100-200 nm.
[0109] Example 7
[0110] In this embodiment, iron-nickel doped carbon nanotubes are prepared in a similar manner to that in embodiment 1, except that step (2) is as follows:
[0111] 1.0 g of Fe / Ni-MIL-88B was weighed and added into 9 mL of DMF, and dispersed by ultrasonication for 2 h. 1 g of polyacrylonitrile (PAN) was added, and stirred at 400 rpm overnight to prepare a spinning solution.
[0112] The LSV curve of the sample was measured in the same manner as in Example 1. The results showed that when the iron-nickel doped carbon nanotubes obtained in this example were used as an electrocatalyst, the half-wave potential was 0.83V.
[0113] Example 8
[0114] In this embodiment, iron-nickel doped carbon nanotubes are prepared in a similar manner to that in embodiment 1, except that step (2) is as follows:
[0115] 2.0 g of Fe / Ni-MIL-88B was weighed and added into 10 mL of DMF, and dispersed by ultrasonication for 2 h. 1 g of polyacrylonitrile (PAN) was added, and stirred at 400 rpm overnight to prepare a spinning solution.
[0116] The LSV curve of the sample was detected in the same manner as in Example 1. The results showed that when the iron-nickel doped carbon nanotubes obtained in this example were used as an electrocatalyst, the half-wave potential was 0.84V.
[0117] Example 9
[0118] In this embodiment, iron-nickel doped carbon nanotubes are prepared in a similar manner to that in embodiment 1, except that step (4) is as follows:
[0119] The obtained PAN / Fe / Ni-MIL-88B polyacrylonitrile nanofiber film is first oxidized and then calcined under inert gas: first, the temperature is increased to 260°C at a heating rate of 1°C / min in air and kept warm for 2 hours, then cooled to room temperature, and then the obtained sample is placed in the downstream of a tubular furnace, and melamine is placed upstream, with a mass ratio of melamine to sample of 10:1. Nitrogen is introduced, and the temperature is increased from 30°C to 700°C at a heating rate of 5°C / min and kept warm for 2 hours. After the product is ground, an iron-nickel doped carbon nanotube material is obtained.
[0120] The LSV curve of the sample was measured in the same manner as in Example 1. The results showed that when the iron-nickel doped carbon nanotubes obtained in this example were used as an electrocatalyst, the half-wave potential was 0.86V.
[0121] Example 10
[0122] In this embodiment, iron-nickel doped carbon nanotubes are prepared in a similar manner to that in embodiment 1, except that step (4) is as follows:
[0123] The obtained PAN / Fe / Ni-MIL-88B polyacrylonitrile nanofiber film is first oxidized and then calcined under inert gas: first, the temperature is increased to 260°C at a heating rate of 1°C / min in air and kept warm for 2 hours, then cooled to room temperature, and then the obtained sample is placed downstream in a tubular furnace, melamine is placed upstream, the mass ratio of melamine to sample is 10:1, nitrogen is introduced, and the temperature is increased from 30°C to 900°C at a heating rate of 5°C / min and kept warm for 2 hours. After the product is ground, the iron-nickel doped carbon nanotube material is obtained.
[0124] The LSV curve of the sample was measured in the same manner as in Example 1. The results showed that when the iron-nickel doped carbon nanotubes obtained in this example were used as an electrocatalyst, the half-wave potential was 0.85V.
[0125] Embodiment 11
[0126] In this embodiment, iron-nickel doped carbon nanotubes are prepared in a similar manner to that in embodiment 1, except that step (4) is as follows:
[0127] The obtained PAN / Fe / Ni-MIL-88B polyacrylonitrile nanofiber film is first oxidized and then calcined under inert gas: first, the temperature is increased to 260°C at a heating rate of 1°C / min in air and kept warm for 2 hours, then cooled to room temperature, and then the obtained sample is placed downstream in a tubular furnace, melamine is placed upstream, the mass ratio of melamine to sample is 10:1, nitrogen is introduced, and the temperature is increased from 30°C to 800°C at a heating rate of 2°C / min and kept warm for 2 hours. After the product is ground, the iron-nickel doped carbon nanotube material is obtained.
[0128] The LSV curve of the sample was measured in the same manner as in Example 1. The results showed that when the iron-nickel doped carbon nanotubes obtained in this example were used as an electrocatalyst, the half-wave potential was 0.77V.
[0129] Comparative Example 1
[0130] In this comparative example, iron-nickel doped carbon nanotubes were prepared in a similar manner to that in Example 1, except that no Fe / Ni-MIL-88B was added to the spinning solution, i.e., step (2) was as follows: 1 g of polyacrylonitrile was weighed and dispersed in 10 mL of N,N-dimethylformamide solution, and stirred overnight to prepare a spinning solution.
[0131] The transmission electron microscope image of the carbon nanotubes obtained in comparative example 1 shows that there is only a carbon skeleton structure. The LSV curve of the sample is detected in the same manner as in example 1. The results show that when the iron-nickel doped carbon nanotubes obtained in this example are used as electrocatalysts, the half-wave potential is 0.73V.
[0132] Comparative Example 2
[0133] In this comparative example, iron-nickel doped carbon nanotubes were prepared in a similar manner to that of Example 1, except that NiCl2·6H2O was not added, but only FeCl3·6H2O was added. That is, step (1) was:
[0134] Weigh 3.24 g FeCl3·6H2O, 1.99 g terephthalic acid (H2BDC) and 60 mL DMF, mix them, stir at 400 rpm for 10 minutes, add 4.8 mL 2M NaOH solution into the above solution, stir at 400 rpm for 15 minutes, pour into a 100 mL autoclave, keep in an oven at 100°C for 3 hours, then cool to room temperature, centrifuge at 6000 rpm for 5 minutes in a centrifuge, wash and centrifuge with DMF and anhydrous ethanol respectively, and dry in a vacuum drying oven at 70°C for 12 hours to obtain Fe-MIL-88B material.
[0135] The LSV curve of the sample was measured in the same manner as in Example 1. The results showed that when the iron-nickel doped carbon nanotubes obtained in this example were used as an electrocatalyst, the half-wave potential was 0.77V.
[0136] It can be seen from this that the present invention assembles an iron-nickel bimetallic organic framework structure in electrospun fibers to effectively improve the electrocatalytic performance of the material.
[0137] The above are merely exemplary embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing iron-nickel doped carbon nanotubes, characterized in that: The steps include: (1) Using a substance containing iron salt, nickel salt and terephthalic acid as raw materials, Fe / Ni-MIL-88B metal organic framework material was prepared by a hydrothermal method; (2) dispersing Fe / Ni-MIL-88B in N,N-dimethylformamide and adding polyacrylonitrile to form a spinning solution; (3) spinning the spinning solution to obtain a polyacrylonitrile fiber film containing Fe / Ni-MIL-88B; (4) The obtained polyacrylonitrile fiber film is placed in air for oxidation, and then carbonized in a nitrogen atmosphere to obtain the iron-nickel doped carbon nanotubes.
2. The preparation method according to claim 1, wherein In step (1), the Fe / Ni-MIL-88B metal organic framework material is prepared by a method comprising the following steps: A substance containing iron salt, nickel salt and terephthalic acid is used as a raw material, added into N,N-dimethylformamide, mixed evenly to form a mixed solution, and a sodium hydroxide solution is added, mixed evenly to obtain a reaction solution, and a hydrothermal reaction is carried out at 100-150° C. to obtain a Fe / Ni-MIL-88B metal organic framework material.
3. The preparation method according to claim 1, wherein In the raw material, the molar ratio of iron element to nickel element is (0.5-2.5):
1.
4. The preparation method according to claim 1, wherein In the raw materials, the molar ratio of the total amount of iron and nickel elements to terephthalic acid is (2-3.5):
1.
5. The preparation method according to claim 1, wherein In step (2), the usage ratio of polyacrylonitrile, N,N-dimethylformamide and Fe / Ni-MIL-88B is 1 g: (8-10) mL: (1-2) g.
6. The preparation method according to claim 1, wherein In step (4), the carbonization process comprises the following steps: The sample obtained after oxidation is placed downstream of a tube furnace, melamine is placed upstream, nitrogen is introduced, and calcination is performed at 700-900°C to complete the carbonization process.
7. An iron-nickel doped carbon nanotube, characterized in that: The invention is prepared by the method according to any one of claims 1 to 6.
8. The iron-nickel doped carbon nanotube according to claim 7, wherein: The iron-nickel doped carbon nanotubes contain carbon, nitrogen, oxygen, iron and nickel. The atomic percentage of the iron is 0.85-1.20 at%, and the atomic percentage of the nickel is 0.90-1.50 at%.
9. An oxygen reduction reaction electrode, characterized in that It comprises an oxygen reduction reaction electrocatalyst, wherein the electrocatalyst comprises the iron-nickel doped carbon nanotube according to claim 7 or 8.
10. Use of the iron-nickel doped carbon nanotubes according to claim 7 or 8, or the oxygen reduction reaction electrode according to claim 9 in the field of electrocatalytic oxygen reduction reaction.
Citation Information
Patent Citations
photocatalyst for in-situ growth of Ni-MOF film on foamed nickel surface, preparation method and application thereof
CN112076791A
Modulated nickel / cobalt bimetal MOF (Metal Organic Framework)-based electrocatalyst as well as preparation method and application thereof
CN114318358A
C3N4-coated carbon nanotube-loaded NiFe bifunctional oxygen electrocatalyst and preparation method thereof
CN113270597A
Preparation and application of Fe-N-CNFs catalyst based on Fe-MIL
CN113889628A
Preparation method of Fe / Cu / N doped porous carbon nanotube and application of Fe / Cu / N doped porous carbon nanotube in electrocatalytic oxygen reduction reaction
CN116623213A